Glucose Metabolic Reprogramming of ER(+) Breast Cancer in Acquired Resistance to the CDK4/6 Inhibitor Palbociclib - Lorito, Nicla (Cells, 2020)
The majority of breast cancers express the estrogen receptor (ER) and are dependent on estrogen for their growth and survival. Endocrine therapy (ET) is the standard of care for these tumors. However, a superior outcome is achieved in a subset of ER positive (ER(+))/human epidermal growth factor receptor 2 negative (HER2(−)) metastatic breast cancer patients when ET is administrated in combination with a cyclin-dependent kinases 4 and 6 (CDK4/6) inhibitor, such as palbociclib. Moreover, CDK4/6 inhibitors are currently being tested in ER(+)/HER2(+) breast cancer and reported encouraging results. Despite the clinical advances of a combinatorial therapy using ET plus CDK4/6 inhibitors, potential limitations (i.e., resistance) could emerge and the metabolic adaptations underlying such resistance warrant further elucidation. Here we investigate the glucose-dependent catabolism in a series of isogenic ER(+) breast cancer cell lines sensitive to palbociclib and in their derivatives with acquired resistance to the drug. Importantly, ER(+)/HER2(−) and ER(+)/HER2(+) cell lines show a different degree of glucose dependency. While ER(+)/HER2(−) breast cancer cells are characterized by enhanced aerobic glycolysis at the time of palbociclib sensitivity, ER(+)/HER2(+) cells enhance their glycolytic catabolism at resistance. This metabolic phenotype was shown to have prognostic value and was targeted with multiple approaches offering a series of potential scenarios that could be of clinical relevance.